LAND SUBSIDENCE IN SEMARANG - SUPRABADEVI A.S.; Takahiro Osawa; I Nyoman Merit (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
This research aims to identify monitoring land subsidence in Semarang has been done using raster data operation of the DEM in GIS environment. Digital representation of relief of Semarang area was generated from a point map which contains elevation data. The last update of the elevation data was made using geodetic, using Global Positioning System (GPS). Decrease in land distribution is estimated from the data of GPS Geodetic years 2008-2011, in the Semarang area north, west, central, east and south. Reduction in the range of 2008-2009 reached -12.4 cm, then increased in 2009-2010 to be -20-4 cm and -10.5 cm fell back to the years 2010-2011. Decline in the face of the land in Hyderabad occurs mainly in the n01th, east, central and south of Semarang. Subsidence causing damage to infrastmcture, buildings, and results in moving tidal lowlands.damage potential economic loss is cracks in buildings and infrastmcture (roads and bridges), the number of homes that have been tilted and nearly drowned. In addition to direct losses, reduction in ground level also cause indirect losses that rob the increasingly widespread flooding in the northern region of Semarang.in 2008- 2010 June-July with a high tide occurs o.6 cm from the surface of the sea water in the area of Semarang.